THE GROWTH OF Cymbidium finlaysonianum Lindl. ORCHID SEEDLING AT VARIOUS CONCENTRATIONS OF FOLIAR FERTILIZER - Susiani, Susiani; Asnawati, Asnawati; Listiawati, Agustina (Jurnal Sains Mahasiswa Pertanian, 2019)
Leaves through fertilization is the alternative supply of nutrients for plants. The giving of foliar fertilizer on post acclimatization seedling needed for using the precise concentration to avoid plant organs from damage. This study aims to find the best concentration of foliar fertilizer on the growth of Cymbidium finlaysonianum orchids. The research was conducted at the shelter house of Agriculture Faculty of Tajungpura University Pontianak which start from Desember 26th 2017 until April 26th 2018. The research used Completely Randomized Design (CRD), consists of 6 concentration treatment levels of Gaviota 63 foliar fertilizer which is k1= 1 g/l, k2= 2 g/l, k3= 3 g/l, k4= 4 g/l, k5= 5 g/l, k6= 6 g/l with 4 replication and 4 sample plants. Â Â Observational variables included the increase of root number, the increase of leaves number, the increase of leaf length, the increase of leaf width and environmental observation. The result showed the given of foliar fertilizer as much 1 g/l to 6 g/l giving the good growth responses towards the increase of root number, the increase of leaves number and the increase of leaf length of Cymbidium finlaysonianum orchid seedling. The giving of 1 g/l foliar fertilizer is the effective concentration for the increase of leaf width and the growth of Cymbidium finlaysonianum orchid seedling.